Análise da agroindústria canavieira nos estados do Centro-Oeste do Brasil a partir da matriz de capacidades tecnológicas - Meurer, Angelica Patricia Sommer (2014)
The objective of this research study was to analyze the technological dynamics of sugarcane agroindustry in the Midwest Region of Brazil, through the instruments of technological capabilities under four areas: investment (initial and running new projects); operation / production (process and product engineering and industrial management), innovation (ability to seek innovations in product and the process of increasing research and development - R & D), and the context of relations with the economy (insertion in the organizational and institutional environment). In order to fulfill this purpose, primary data were collected from plants and distilleries through the application of questionnaires in loco (answered 100% of the units of Mato Grosso State, 54.5% of Mato Grosso do Sul State and 50% Goias State). In conclusion, it was observed that the sugarcane agroindustries of the three states (MT, MS and GO) dominate much of technological capabilities in the basic gradation (simple routine) and intermediate gradation (adaptive duplicative). However, regarding the advanced gradation (innovative risky), which is the one that allows higher competitive excellence, there were the lowest percentages of occurrences in each state. Therefore, it becomes urgent that the industry directs efforts to grow in the design of the basic process and to manufacture equipment, in its own process innovation in R & D, which will facilitate the creation of new technologies, the patenting and subsequent sale of technological packages. Overall, it was found that Goias presented the highest technical concentration, standing out in relation to Mato Grosso and Mato Grosso do Sul in several profiles of technological capabilities matrix.